Elafibranor restricts lipogenic and inflammatory responses in a human skin stem cell-derived model of NASH. (June 2019) - Boeckmans, Joost; Buyl, Karolien; Natale, Alessandra; Vandenbempt, Valerie; Branson, Steven; De Boe, Veerle; Rogiers, Vera; De Kock, Joery; Rodrigues, Robim M.; Vanhaecke, Tamara
Graphical abstract: Abstract: Non-alcoholic steatohepatitis (NASH) is characterized by hepatocellular steatosis with concomitant hepatic inflammation. Despite its pandemic proportions, no anti-NASH drugs have been approved yet. This is partially because drug development is decelerated due to the lack of adequate tools to assess the efficacy of potential new drug candidates. The present study describes the development and application of a new preclinical model for NASH using hepatic cells generated from human skin-derived precursors. Exposure of these cells to lipogenic (insulin, glucose, fatty acids) and pro-inflammatory factors (IL-1β, TNF-α, TGF-β) resulted in a characteristic NASH response, as indicated by intracellular lipid accumulation, modulation of NASH-specific gene expression, increased caspase-3/7 activity and the expression and/or secretion of inflammatory markers, including CCL2, CCL5, CCL7, CCL8, CXCL5, CXCL8, IL1a, IL6 and IL11. The human relevance of the proposed NASH model was verified by transcriptomics analyses that revealed commonly modulated genes and the identification of the same gene classes between the in vitro system and patients suffering from NASH. The application potential of this in vitro model was demonstrated by testing elafibranor, a promising anti-NASH compound currently under clinical phase III trial evaluation. Elafibranor attenuated in vitro key features of NASH, and dramatically lowered lipid load as well as the expression and secretion of inflammatory chemokines, which in vivo are responsible for the recruitment of immune cells. This reduction in inflammatory response was NFκB-mediated. In summary, this human-relevant, in vitro system proved to be a sensitive testing tool for the investigation of novel anti-NASH compounds.